(untitled) (Argos, 2024)
The Gospel of Philip –the third place in the Codex II of the Library of Nag Hammadi– is composed of six other treatises arranged in chronological order as follows: The Apocryphon (secret book) of John (long version); The Gospel of Thomas; The Hypostasis of the Archons; On the Origin of the World (first copy); The Exegesis on the Soul and The Book of Thomas, the Contender. The Gospel of Philip is the most "sacramental" of the Gnostic gospels, since the five main rites: baptism, anointing, the Eucharist, redemption and the bridal chamber are directly mentioned as constituents of a single mystery. Those descriptions are preceded by anthropomorphisms of God, such as "dyer" and "man-eater", as well as by names assigned to divine realities which embrace an esoteric sense inherent to the Valentinian school.